LB-006 Increased intracranial and systemic VCAM1 relates to hypertension and reduced percent change in NIHSS after mechanical thrombectomy. (6th August 2020) - Maglinger, B; Sands, M; Frank, J; Trout, A; Roberts, J; Grupke, S; Turchan-Cholewo, J; Stowe, A; Fraser, J; Pennypacker, K
Abstract : Introduction: The University of Kentucky Blood and Clot Thrombectomy Registry and Collaboration (BACTRAC) protocol (clinicaltrials.gov NCT03153683 ) utilizes thrombectomy to isolate intracranial (i.e. distal to thrombus) arterial blood and systemic (i.e. carotid) arterial blood from thrombectomy procedures to better understand stroke. The objective of this study within that protocol was to investigate the relationship among Vascular Cell Adhesion Molecule 1 (VCAM1), hypertension (HTN), and stroke recovery in patients undergoing mechanical thrombectomy for emergent large vessel occlusion (ELVO) stroke. Here, we report how intracranial and systemic proteomic expression levels relate to HTN and the change in National Institute of Health Stroke Scale/Score (NIHSS) from admittance to discharge. Methods: Intracranial and systemic plasma samples from 25 subjects underwent cardiometabolic proteomic analysis at Olink Proteomics (Olink Proteomics, Boston, MA). VCAM1 expression levels were reported as a Normalized Proteomic eXpressoin (NPX) for each subject. Demographic data were also reported including HTN and both admission NIHSS and discharge NIHSS. Linear regression analysis was run on both intracranial and systemic VCAM1 expression levels against% change in NIHSS ((Admittance NIHSS - Discharge NIHSS)/Admittance NIHSS)). Two-tailed t-tests were run assessing VCAM1 expression with hypertension (HTN) vs. no hypertension. Data analysis was performed using IBM SPSS Statistics. Results: Linear regression analysis demonstrated increased expression of intracranial VCAM1 significantly correlated with a smaller% change in NIHSS (p=0.001). Similarly, increased systemic VCAM1 expression was also found to have a significant relationship with smaller% change in NIHSS (p=0.005). Subjects with hypertension had significantly higher intracranial (p=0.03) and systemic (p=0.001) VCAM1 levels compared to those without HTN. Discussion: VCAM1 mediates leukocyte-endothelial cell adhesion and has been shown to play a role in atherosclerotic plaques, endothelial integrity and function, and stroke recurrence. This study takes a novel approach of sampling both intracranial and systemic arterial blood during an ELVO stroke. We found increased intracranial and systemic VCAM1 independently correlate with a smaller% change in NIHSS. Although preliminary, these results may suggest an informative role of VCAM1 levels at the time of infarct. Additionally, within our cohort, those with HTN had higher levels of intracranial and systemic VCAM1. These data are in line with previous studies suggesting VCAM1 may be a marker of endothelial damage due to HTN. To better understand our findings, we plan to perform subset analyses investigating VCAM1 levels in relation to stroke recurrence, dyslipidemia, infarct time and infarct volume. As VCAM1 plays a role in leukocyte recruitment during the inflammatory state, we also plan to investigate how the antioxidant superoxide dismutase 1 (SOD1) may modulate intracranial and systemic levels of VCAM1 and influence functional recovery based on NIHSS. Disclosures: B. Maglinger: None. M. Sands: None. J. Frank: None. A. Trout: None. J. Roberts: None. S. Grupke: None. J. Turchan-Cholewo: None. A. Stowe: 4; C; Cerelux, LLC. J. Fraser: 2; C; Stream Biomedical, Medtronic, Penumbra. 4; C; Cerelux, LLC; Fawkes Biotechnology. K. Pennypacker: 4; C; Cerelux, LLC.